Surface Morphology Study of Nanostructured Lead-Free Solder Alloy Sn-Ag-Cu Developed by Electrodeposition: Effect of Current Density Investigation - Sakinah Mohd Yusof; Abdul Hadi; Junaidah Jai (Chemical Engineering Diponegoro University, 2013)
Nanostructured lead-free solder Sn-Ag-Cu (SAC) was developed by electrodeposition method at room temperature. Electrolite bath which comprised of the predetermined quantity of tin methane sulfonate, copper sulfate and silver sulfate were added sequentially to MSA solution. The methane sulphonic acid (MSA) based ternary Sn-Ag-Cu bath was developed by using tin methane sulfonate as a source of Sn ions while the Cu+ and Ag+ ions were obtained from their respective sulfate salts. The rate of the electrodeposition was controlled by variation of current density. The addition of the buffer, comprising of sodium and ammonium acetate helped in raising the pH solution. During the experimental procedure, the pH of solution, composition of the electrolite bath, and the electrodeposition time were kept constant. The electrodeposited rate, deposit composition and microstructure were investigated as the effect of current density. The electrodeposited solder alloy was characterized for their morphology using Field Emission Scanning Electron Microscope (FESEM). In conclusion, vary of current density will play significant role in the surface morphology of nanostructured lead-free solder SAC developed. Doi: 10.12777/ijse.5.2.51-55 [How to cite this article: Yusof, S.M., Hadi, A., and Jai, J. (2013). Surface Morphology Study of Nanostructured Lead-Free Solder Alloy Sn-Ag-Cu Developed by Electrodeposition: Effect of Current Density Investigation. International Journal of Science and Engineering, 5(2):51-55. Doi: 10.12777/ijse.5.2.51-55